Prevalence and correlates of anxiety and stress in school going adolescents in Delhi national capital region: a cross sectional study - Khanna, Tejasvini; Banerjee, Bratati; Majhi, Madan Mohan (International Journal Of Community Medicine And Public Health, 2023)
Background: Anxiety and stress are notable health problems plaguing adolescents. Moreover, issues such as poor sleep quality and body image issues, common in adolescence, have also been linked to anxiety and stress previously. Methods: A cross sectional study was conducted across 392 school going adolescents in Delhi NCR, India. Sociodemographic and lifestyle data was collected using a pre-tested semi-structured questionnaire. DASS-21 was used to screen the participants for anxiety and stress, Pittsburgh sleep quality index for sleep quality, and Stunkard figure rating silhouette for body image issues. Data was entered into MS Excel spreadsheets and Statistical Package for Social Sciences version-25 was used for analysis. Results: 47.5% participants suffered from anxiety and 22.2% from stress. Anxiety was significantly associated with father’s education and occupation, stressful occurrences in the family, poor sleep quality and inadequate exercise. Stress was significantly higher in females and those with poor sleep quality. Conclusions: Anxiety and stress in adolescents show significant associations with familial and lifestyle factors. Identifying these risk factors can enable timely diagnosis and intervention.